Prevalence, healthcare resource utilization and overall burden of fungal meningitis in the United States. Issue 2 (February 2018) - Charalambous, Lefko T.; Premji, Alykhan; Tybout, Caroline; Hunt, Anastasia; Cutshaw, Drew; Elsamadicy, Aladine A.; Yang, Siyun; Xie, Jichun; Giamberardino, Charles; Pagadala, Promila; Perfect, John R.; Lad, Shivanand P.
Abstract : Purpose. : Previous epidemiological and cost studies of fungal meningitis have largely focused on single pathogens, leading to a poor understanding of the disease in general. We studied the largest and most diverse group of fungal meningitis patients to date, over the longest follow‐up period, to examine the broad impact on resource utilization within the United States. Methodology. : The Truven Health Analytics MarketScan database was used to identify patients with a fungal meningitis diagnosis in the United States between 2000 and 2012. Patients with a primary diagnosis of cryptococcal, Coccidioides, Histoplasma, or Candida meningitis were included in the analysis. Data concerning healthcare resource utilization, prevalence and length of stay were collected for up to 5 years following the original diagnosis. Results. : Cryptococcal meningitis was the most prevalent type of fungal meningitis (70.1 % of cases over the duration of the study), followed by coccidioidomycosis (16.4 %), histoplasmosis (6.0 %) and candidiasis (7.6 %). Cryptococcal meningitis and candidiasis patients accrued the largest average charges ($103 236 and $103 803, respectively) and spent the most time in the hospital on average (70.6 and 79 days). Coccidioidomycosis and histoplasmosis patients also accrued substantial charges and time in the hospital ($82 439, 48.1 days; $78 609, 49.8 days, respectively). Conclusion. : Our study characterizes the largest longitudinal cohort of fungal meningitis in the United States. Importantly, the health economic impact and long‐term morbidity from these infections are quantified and reviewed. The healthcare resource utilization of fungal meningitis patients in the United States is substantial.